Theoretical Construction of an Intercultural Counseling Module for Addressing Bullying in Multicultural Elementary Schools - Muhammad Ferdiansyah; Muhammad Alridho Lubis; Zubaidah Zubaidah; Muhammad Zulfikar (Kuras Institute, 2026)
Bullying in multicultural elementary schools in Jambi Province has shown a significant increase, posing serious risks to children’s psychosocial development. This study aims to explore the experiences of teachers, counselors, and students in addressing bullying, identify intercultural values relevant to counseling practices, and construct a conceptual framework for an intercultural counseling module grounded in Jambi’s local wisdom. A qualitative Grounded Theory approach was employed, with data collected through in-depth interviews, participant observation, and focus group discussions. Data were analyzed using open, axial, and selective coding, and validated through source triangulation and expert review. The findings indicate that bullying is influenced by individual factors, socio-cultural dynamics, and school environmental conditions. The analysis resulted in a conceptual model of an intercultural counseling module integrating cross-cultural empathy, local wisdom, and preventive and curative strategies. The study contributes a culturally grounded and practice-oriented framework to advance intercultural guidance and counseling in multicultural elementary school settings